Implementation of Women's Rights in Divorce Sues at the Religious Court of Jepara - Arpangi, ‎; Hidayati, Ita Puspitasari (KnE Social Sciences, 2025)
The research aims to examine and analyze the regulation of women’s rights in divorce lawsuits. The research method used is legal research with a sociological legal approach, analyzed using feminist legal theory, progressive legal theory, and the theory of justice in Islamic law. The results of the study show that the regulation of women’s rights in divorce lawsuits at the Religious Court is very important to guarantee legal protection, justice, and the welfare of women after divorce. Based on Law No. 1 of 1974 and the Compilation of Islamic Law, women have the right to iddah, mut’ah, joint property, child custody, and child support. The justice approach through progressive law, feminist legal theory, and Islamic law strengthens protection for women who are often marginalized economically and socially. The Jepara Religious Court together with stakeholders must actively conduct legal socialization and provide execution funding assistance through the APBD (Regional Revenue and Expenditure Budget) or Village Funds to facilitate access to justice for women after divorce.